2019
DOI: 10.1038/s41598-019-42425-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial agent susceptibilities of Legionella pneumophila MLVA-8 genotypes

Abstract: Legionella pneumophila causes human lung infections resulting in severe pneumonia. High-resolution genotyping of L. pneumophila isolates can be achieved by multiple-locus variable-number tandem-repeat analysis (MLVA-8). Legionella infections in humans occur as a result of inhalation of bacteria-containing aerosols, thus, our aim was to study the antimicrobial susceptibilities of different MLVA-8 genotypes to ten commonly used antimicrobial agents in legi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
2
17
0
2
Order By: Relevance
“…The effectiveness of quinolones—ciprofloxacin, this time—was recorded in a later study by Sikora A. et al [ 46 ]. Contrary to these findings, it was Sharaby et al [ 30 ] who revealed some slight resistance against quinolones but an effectiveness of doxycycline, clarithromycin, rifampicin and trimethoprim sulphamethoxazole (SXT). Nevertheless, despite the finding of the potency of rifampicin, it should be noted that this antibiotic is not suggested for monotherapy due to the rapid appearance of resistance [ 47 ].…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The effectiveness of quinolones—ciprofloxacin, this time—was recorded in a later study by Sikora A. et al [ 46 ]. Contrary to these findings, it was Sharaby et al [ 30 ] who revealed some slight resistance against quinolones but an effectiveness of doxycycline, clarithromycin, rifampicin and trimethoprim sulphamethoxazole (SXT). Nevertheless, despite the finding of the potency of rifampicin, it should be noted that this antibiotic is not suggested for monotherapy due to the rapid appearance of resistance [ 47 ].…”
Section: Resultsmentioning
confidence: 92%
“…However, it was, again, one of the less active agents. By contrast, Sharaby et al [ 30 ] studied several environmental and clinical genotypes and revealed a discrepancy in antimicrobial agents’ susceptibilities, even in environmental strains that were isolated from adjacent points of the same water system. This is of importance considering that in some cases, the pneumonia caused by Legionella infection may hide a mixture of L. pneumophila strains [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For clinical reasons, genotyping should allow for a distinction with respect to virulence traits and antibiotic resistance [80]. Sharaby et al [81,82] showed that L. pneumophila isolates from Israel had MLVA-8 genotype-specific virulence traits. Even their resistance to antibiotics showed a strong correlation with the MLVA-genotypes.…”
Section: Genotyping Using Mlva-what Resolution Is Needed For Ecologicmentioning
confidence: 99%